Global Threats From Preventable Injuries. (October 2017) - Phillips, Jennan A.
Preventable injuries kill thousands of the world's population every day and injure millions each year. Road traffic crashes and opioid drug misuse are major causes of these injuries. Increased efforts are needed to promote strong policies, develop new prevention strategies, and protect workers from these global public health threats.